Contamination of lard and other animal fat in palm olein used in the frying of meats - Idarmawi, Khairatul Munirah (2016)
A study was conducted to determine the contamination of lard and other animal fats in palm olein used in the frying of meats such as beef, chicken and pork. The meats were fried in the palm olein at 180 oC and the used palm olein were collected and analysed using gas chromatography, high performance liquid chromatography and differential scanning calorimetry. The differential scanning calorimetry heating profiles proved that the existing of the endothermic peak ‘X’ in the temperature region from 4.7 oC to 6.5 oC, the sharp exothermic curve ‘Z’ in the temperature region from 4.2 oC to 4.3 oC and the endothermic peak ‘B6’ in the temperature region from 10.7 oC to 13.9 oC simultaneously, indicated the contamination from the frying of beef, whereas, the presence of the sharp exothermic curve ‘Z’ in the temperature region from 4.9 oC to 6.6 oC only, was clearly indicated the contamination from the frying of pork. Frying of chicken meat in the palm olein did not obviously influence the heating and cooling profiles of the used palm olein. Thus, differential scanning calorimetry is found to be very useful, safe, fast, sensitive, efficient and reliable instrumental method in determining the fingerprint of lard contamination in the palm olein used in the frying of meats. The Principle Component Analysis of triacylglyceride compositions and the heating profiles were able to classify the palm olein used in the frying of meats into two groups. The first group comprised of the palm olein used in the frying of pork, pork sausages and bacon, whereas, the second group comprised of the palm olein used in the frying of beef and chicken. Therefore, the findings obtained in this study can be applied to the determination and certification of halal status especially in food industries.